ผลการบริบาลทางเภสัชกรรมต่อคุณภาพชีวิตด้านการบำบัดด้วยยาใน ผู้ป่วยโรคมะเร็งที่ได้รับยาเคมีบำบัด : การทดลองแบบสุ่มและมีกลุ่มควบคุม - ภรณ์ทิพย์ สร้อยพิทักษ์ (คณะเภสัชศาสตร์ มหาวิทยาลัยสงขลานครินทร์, 2022)
Objectives:To determine drug therapy-related quality of life in cancer patients receiving pharmaceuticalcarecompared to those receiving usual. Method:This study was a single-blinded randomized controlled trial in cancer patients receiving chemotherapy at SamutprakarnHospital.The study comparedthe groups receiving pharmaceutical care by providing knowledge and counseling on disease/drug/adverse drug reactions and self-care practice of patients receiving chemotherapy, identifying and resolving drug-related problems, with the controlgroup receiving usual care of the Hospital. The primary outcome was drug therapy-related quality of life as measured by the Patient-Reported Outcomes Measure of Pharmaceutical Therapy for Quality of Life (PROMPT-QoL) before and after the provision of pharmaceutical care for both groups. Changes of quality of life of both groups were comparedusing independentsample t-test.The study was conducted during November 2020–February 2021.Results:Differences in drug therapy-related quality of life scores assessed by the PROMPT-QoL between the first and second measurement in study group were higher than those in the control groupin alldimensions of the scale (P<0.01). Overall scores improvedby17.48±9.43 and 3.08±5.90 in the study and control groups, respectively, which differed statistically (P<0.001). Conclusion:Pharmaceutical care provision increased drug therapy-related quality of life among cancer patients receiving chemotherapy more than usual caredid. Therefore, such service should be encouraged for cancer patients receiving chemotherapy.